A clinical trial evaluation of handwashing products and educational resources to improve hand hygiene in paediatric patients and school children - McNicholl, Johanna; Younie, Sarah; Crosby, Sapphire; Laird, Katie (Frontiers in Public Health, 2024)
Introduction: It is widely acknowledged that good hygiene (HH) is an important non-pharmaceutical method for reducing the transmission of infectious diseases. Children are at high risk of infection due to their immature immune systems. Hospital transmitted infections are a cause for concern worldwide, with poor HH suggested to be responsible for up to 20% of cases. Patients, in particular paediatric patients, are often overlooked when it comes to the promotion of hand hygiene compliance (HHC) in hospitals. This report describes the clinical evaluation of the 'Soaper Stars'; a collection of child-friendly HH products with linked educational resource, developed using the COM-B approach to behaviour change, and designed to encourage correct HH in paediatric patients and in schools. Method: The Soaper Star products were distributed on paediatric wards in five UK hospitals, and the use of the products around mealtimes was evaluated. Workshops teaching the 'why when and how' of handwashing were run in four UK primary schools with pre and post evaluations conducted to establish impact on knowledge. Over 300 children were involved. Results: The Soaper Stars products stimulated a 38% increase in HHC compared to when only hospital-issued products were available, and verbal feedback from families indicated that having the Soaper Star products encouraged improved HHC by all visitors, not just the patient. Workshops in four schools (283 pupils) showed an increase in knowledge around the transmission of infection and the need for good HH that was sustained for at least 4 weeks. Conclusion: The Soaper Stars products stimulated a 38% increase in HHC compared to when only hospital-issued products were available, and verbal feedback from families indicated that having the Soaper Star products encouraged improved HHC by all visitors, not just the patient. Workshops in four schools (283 pupils) showed an increase in knowledge around the transmission of infection and the need for good HH that was sustained for at least 4 weeks.